2022
DOI: 10.1590/fst.118521
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the antioxidant and mineral contents of raspberry varieties

Abstract: Humans maintain their health by consuming a variety of vegetables and fruits that contain antioxidants, both enzymatic and no enzymatic. Raspberry is one of the most diverse genus of true dicotyledonous plants, which includes 12 subspecies and about 429 species. Raspberry fruit is rich in antioxidant compounds, especially polyphenols. Two species of raspberry were studied to determine the amount of antioxidants and phenolic and flavonoid compounds in their fruits at three different stages of fruit ripening imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Previous studies also reported the presence of tannins in plum fruit. Soluble tannins present in plum peels were found to be 59.9–113.9 mg EE/100 g FW and in fruit flesh were about 31.4–58.2 mg EE/g FW 33 . Similar pattern of the presence of tannin was seen in our study with plum showing the maximum tannin amount while guava and pomegranate displaying the minimum.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Previous studies also reported the presence of tannins in plum fruit. Soluble tannins present in plum peels were found to be 59.9–113.9 mg EE/100 g FW and in fruit flesh were about 31.4–58.2 mg EE/g FW 33 . Similar pattern of the presence of tannin was seen in our study with plum showing the maximum tannin amount while guava and pomegranate displaying the minimum.…”
Section: Resultssupporting
confidence: 88%
“…Polyphenol in jamun was found to be 203 mg GAE/100 g of fresh fruit pulp 32 . TPC in fruit peel was observed to be 128.5–2020 mg ellagic acid equivalents (EE)/100 g fresh weight (FW) while in plum fruit flesh, it was estimated to be around 260.9–1080.9 mg EE/100 g FW 33 . Table 3 shows the mean and standard deviation of the TTC of all seven fruit extracts with 95% confidence intervals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans maintain their health by eating healthy fruits and vegetables having antioxidants. The antioxidants vary according to variety and ripening stage of fruits (Shoukat et al, 2022).…”
Section: Tfcmentioning
confidence: 99%